Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1108/13552549810222939
|View full text |Cite
|
Sign up to set email alerts
|

Direct laser freeform fabrication of high performance metal components

Abstract: This paper focuses on recent advances in direct freeform fabrication of high performance components via selective laser sintering (SLS). The application, known as SLS/HIP, is a low cost manufacturing technique that combines the strengths of selective laser sintering and hot isostatic pressing (HIP) to rapidly produce low volume or “one of a kind” high performance metal components. Direct selective laser sintering is a rapid manufacturing technique that can produce high density metal parts of complex geometry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 8 publications
0
62
0
Order By: Relevance
“…SLS is largely similar to the conventional PM and this explains that the microstructure of SLS Ti-6Al-4V is close to that of equilibrium state as with the PM or cast Ti-6Al-4V [79][80][81][82][83][84][85][86][87][88]. Figure 8 compares the microstructure of SLS Ti-6Al-4V with that of an HIP Ti-6Al-4V [81].…”
Section: Microstructure Of Sls Ti-6al-4vmentioning
confidence: 96%
See 1 more Smart Citation
“…SLS is largely similar to the conventional PM and this explains that the microstructure of SLS Ti-6Al-4V is close to that of equilibrium state as with the PM or cast Ti-6Al-4V [79][80][81][82][83][84][85][86][87][88]. Figure 8 compares the microstructure of SLS Ti-6Al-4V with that of an HIP Ti-6Al-4V [81].…”
Section: Microstructure Of Sls Ti-6al-4vmentioning
confidence: 96%
“…EOSINT M250X and EOISNT M270 are being used as the SLS machines for preparing AM Ti-6Al-4V [79][80][81][82][83][84][85][86][87][88]. The general working conditions and key machine/processing parameters are shown by Figure 5 and listed in Table 6.…”
Section: Selective Laser Sintering (Sls)mentioning
confidence: 99%
“…5,49,61 This process mainly uses the CO 2 laser 7,9,36 as the heat source but an Nd:YAG laser has also been employed either independently 9,10,16,42,45,62 or in combination with a CO 2 laser as in the dual-beam technique. 4,41 In addition, diode lasers have been used to sinter a metal mixture and sand.…”
Section: Methodsmentioning
confidence: 99%
“…The materials include wax, cermet, ceramics, nylon/glass composite, metal-polymer powders, metals, alloys or steels, 7,9 polymers, 33,34 nylon, and carbonate. 35,36 Polycarbonate powders [36][37][38] and Bishphenol-A polycarbonate 39 12 and alloys (e.g., cobalt-based, nickelbased, 42,44 bronze-nickel, 19 pre-alloyed bronze-nickel, 28 Inconel 625, Ti6Al-4V, 45 stainless steel, 4 gas-atomized stainless steel 316L, 9,16,17 AISI 1018 carbon steel, 46 high-speed steel, 7,47 precoated foundry sand, 22 and alumina with polymer binder) 48 were tested for laser sintering. The results demonstrated that any material can be combined with a low-melting-point material that will serve as glue.…”
Section: Methodsmentioning
confidence: 99%
“…The lasers equipment originally used could only melt materials with low melting points, for instance brass, and was not powerful enough to completely melt steel. Therefore, this manufacturing method could not meet the requirements for parts subjected to high stress levels or elevated temperatures, e.g., superalloys [4]. With time, the process control was improved and more powerful lasers were developed.…”
Section: Introductionmentioning
confidence: 99%